2009
DOI: 10.2223/jped.1904
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli and bifidobacteria in the feces of schoolchildren of two different socioeconomic groups: children from a favela and children from a private school

Abstract: Objective: To determine the number of lactobacillus and bifidobacterium colonies in the feces of schoolchildren from two different socioeconomic levels. Methods:We analyzed fecal samples of children aged 6 to 10 years without gastrointestinal symptoms or recent use of antimicrobials. The first group included 86 children living in a favela in the city of Osasco, state of São Paulo, southeastern Brazil. The second group included 36 children attending a private school in the same city. Body mass index (BMI) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Such diet–microbiota associations have also been reported in varying geographical backgrounds, e.g. subjects from rural Africa or Europe (De Filippo et al, 2010) or other different countries (Lozupone et al, 2012; Yatsunenko et al, 2012; Nakayama et al, 2015) or from different socioeconomic groups (Benno et al, 1989; Mello et al, 2009; Claesson et al, 2012). These studies consistently suggested the diet–microbiota interaction and also its consequent influence on fecal short chain fatty acid concentrations.…”
Section: Discussionmentioning
confidence: 77%
“…Such diet–microbiota associations have also been reported in varying geographical backgrounds, e.g. subjects from rural Africa or Europe (De Filippo et al, 2010) or other different countries (Lozupone et al, 2012; Yatsunenko et al, 2012; Nakayama et al, 2015) or from different socioeconomic groups (Benno et al, 1989; Mello et al, 2009; Claesson et al, 2012). These studies consistently suggested the diet–microbiota interaction and also its consequent influence on fecal short chain fatty acid concentrations.…”
Section: Discussionmentioning
confidence: 77%
“…) (De Filippo et al ., ; Rampelli et al, 2015; Nakayama et al ., 2015). Apart from these factors, the differences observed between school children attending private schools compared to children living in impoverished conditions may be the result of several social factors which are presently difficult to deconvolute (De Mello et al ., ). These factors likely also contribute to the described association between taxonomic structures and level of education (Ding and Schloss, ).…”
Section: Age‐independent Influences On the Git Microbiome And Its Modmentioning
confidence: 97%
“…In spite of the relatively conserved, characteristic features of body site‐specific microbiota (Kurokawa et al ., ; Huttenhower et al ., ; Hollister et al ., ), it remains unclear which factors influence microbial community assembly and their relative importance. Key factors which likely influence microbiota compositions include age (Palmer et al ., ; Mariat et al ., ; Koenig et al ., ), geographical location (Yatsunenko et al ., ), host genetics (Gagliani et al ., ; Blekhman et al ., ), social context (De Mello et al ., ; Koenig et al ., ; Nakayama et al ., 2015), and diet (David et al ., ) (Fig. ).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 98%
“…1 The authors suggest a relation between nutritional status and gastrointestinal flora, since a low number of Lb and Bif was associated with a low body mass index. 1 Whether this association should be regarded as "causal" or more as a have an increased contact with pathogens since they have almost no legal water supply connection and no garbage collection. In conclusion: "the more lactobacilli, the better" seems to be a reality.…”
Section: In This Issue De Mello Et Al Report That Lactobacilli (Lb)mentioning
confidence: 99%